Challenging the Phenomena of Technology - Hayler, M. author. aut Link
IX, 251 p.
Keywords: What is 'technology'? What does it help us to do? What does it force us to consider about our experience of being in the world? In Challenging the Phenomena of Technology, technology is positioned as an experience with specific features, rather than as a class of objects, and this enables a reflection on the ways in which amateurs and experts interact with the artefacts that all humans rely upon. Using e-readers, such as the Kindle and iPad, as a case study, Hayler argues that the use of technology is both more complicated and more human than public discussion often gives it credit for, forcing us to consider its impacts on perception, cognition, and what it means to know anything at all.